Studi karakteristik gerusan lokal pada beberapa tipe pilar jembatan - Sarwono Sarwono (Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2016)
The local scouringcharacteristicsuroundings several bridge pillars forms have a different characteristics, some forms of pillars of the bridge are considered optimum when equipped with the data: discharge, slope of riverbed, material, and on the same flow direction, that will produce the most shallow scouring. The objective of this study is to find the form of pillars that will generate the most superficial scouring. The study is conducted at the Laboratory of River in Surakarta. The used flume has length of 10.00 m, width 0.40 m and height of 0.40 m. The forms of pillar studied are two cylindrical pillars, sheet pile and full walls pillar. The slope of the riverbed (i) are varied, there are three: 0.006, 0.0125 and 0.020. The flow discharge rate there are five variations: 5,37 m3/s, 8,94 m3/s, 12,52 m3/s, 14,31 m3/s, 17,89 m3/s. Land was used at material for river bed, and, there are three kinds of value D50: 0.60 mm, 0.80 mm and 1.00 mm. The research method includes: a field survey, two dimension physical model test with 1:20 scale.The results showed for each pillar shapes have different characters. The deepest scouring suroundings the pillar beside the point, at the beginning of the first minute to the 20th minute in a sudden deep scour the riverbed and form of river bed suroundings are the pillars up and down irregularly. In the 20th minute until the end of the stream scouring decreased almost linearly lines are horizontzl. In general the pile type pillars was found to cause the minimum scouring than other pillar shapes.